Noise Calculation Technique Using Time Varying Model - Saber Izadpanah Tous; Mahmoud Behroozi; Ehsan Kargaran; Hooman Nabovati (Majlesi Journal of Electrical Engineering)
All oscillators are periodically time varying systems, so to accurate phase noise calculation and simulation, time varying model should be considered. Phase noise is an important characteristic of oscillator design. It defined as the spectral density of the oscillator spectrum at an offset from the center frequency of the oscillator relative to the power of the oscillator. In this paper, we study linear time invariant (LTI) and linear time variant (LTV) modelâs to calculate phase noise. Moreover, we propose a simple method for Impulse Sensitivity Function (ISF) calculation. Different oscillators have been selected to evaluate the proposed method.  Simulation results show that the proposed method is simpler than other methods, and we can easily simulation ISF.åªè²è¨ç®æè¡ä½¿ç¨æè®æ¨¡åæè¦ææçæ¯çªå¨é±ææè®ç³»çµ±ï¼æä»¥è¦ç²¾ç¢ºçç¸ä½åªè²çè¨ç®åæ¨¡æ¬ï¼é¨æéè®åçæ¨¡å¼æè©²è¢«èæ®ãç¸ä½åªè²æ¯æ¯çªå¨è¨è¨çä¸åéè¦ç¹å¾µãå®å®ç¾©çºæ¯çªå¨é »èä¸çä¸åå¾ç¸å°æ¼æ¯çªå¨çåççæ¯çªå¨çä¸å¿é »çåç§»çé »èå¯åº¦ãå¨æ¬æä¸ï¼æåç ç©¶äºç·æ§æä¸è®ï¼LTIï¼åç·æ§æè®ï¼LTVï¼æ¨¡åä¾è¨ç®ç¸ä½åªè²ãæ¤å¤ï¼æåæåºäºèè¡éæåº¦å½æ¸ï¼ISFï¼è¨ç®çç°¡å®æ¹æ³ãä¸åæ¯çªå¨å·²é¸å®ï¼è©ä¼°äºè©²æ¹æ³ãä»¿ççµæè¡¨æï¼è©²æ¹æ³æ¯å¶ä»æ¹æ³æ´ç°¡å®ï¼æåå¯ä»¥å¾å®¹æå°æ¨¡æ¬ISFã